Spain : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Spain has experienced income convergence consistently in the past decade, despite gradual losses in competitiveness. The empirical evidence indicates that overall EU enlargement offers a range of opportunities for Spain, points to potential pressures in specific sectors, and offers challenges, and tackling the challenges requires a flexible economy. The pattern of Spanish exports is dominated by its off-center location in the Southern part of the EU. Geographical location also plays a central role in determining the origin of foreign direct investment (FDI) flows to Spain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet